(untitled) (Orfeu, 2024)
This article aims to study the process of artistic re-evaluation of the musicians of the São Paulo State Symphony Orchestra during the period of its reorganization. To do this, we will mobilize the notion of vocational rationality by articulating the analysis of the trajectories of individuals and institutions that create and promote new evaluation criteria for orchestral musicians. Based on an analysis of the orchestra’s archives and semi-structured interviews, we will show the emergence of a new orchestral anatomy after the re-evaluation auditions, transforming Osesp into a more feminine, youthful and international orchestra. However, during this transformation, conflicts and tensions formed mainly around the “old” and “new” musicians of the orchestra, who adhere to different professional values: for the first ones, loyalty between institution and employees, and for the second ones, competence and excellence of work.